Study on Improving Student Reading Comprehension by Using Comic Strips - Sumual, Windyas Desrianti; Darmawan, Darmawan; Wahyudin, Wahyudin (English Language Education, Universitas Internasional Batam, 2025)
This study examines the use of comic strips in improving students' reading comprehension in various educational contexts. The results of the analysis show that the use of comic strips is effective in improving reading comprehension scores, as well as encouraging students' interest, active participation, enthusiasm, and excitement in learning. For example, at SMA MUHAMMADIYAH 7 Serbelawan, the use of comic strips significantly increased the average reading comprehension score compared to the control class. At SMPN 13 Palu, the integration of comic strips in reading learning showed a marked increase in scores, supported by statistical analysis that supported the results. Recommendations were given to integrate comic strips in English teaching practice to improve the effectiveness of reading learning. In addition, it is hoped that the use of this comic strip can have a positive impact on improving students' reading comprehension, where some students still experience difficulties in understanding a text.Overall, this study confirms that comic strips are an effective learning medium for improving students' reading comprehension and enriching their learning experience.